A Study of Histochemical Characteristics of Mucosubstances in Normal Endocervical Glands - Swapna Shedge A1 , Padmaja. A Havle2 , Megha A. Doshi3, Priya Roy4 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: The apical epithelial surfaces of mammalian respiratory, gastrointestinal, and reproductive tracts are coated by mucus, a mixture of water, ions, glycoproteins, proteins, and lipids. Mucins are mainly of two types- Neutral and Acidic. Mucus plays an important role in reproductive function and defence of the female reproductive tract. Objectives: To know the mucin distribution in normal endocervical glands. Methodology: This is a retrospective, observational , analytical, case control study aimed to evaluate mucin histochemical pattern in normal endocervical glands. Ten histologically proven blocks of normal endocervical glands were taken. Tissue sections were stained by, PAS, PAS-diastase, Phenylhydrazine-PAS, Alcian blue pH 2.5, Alcian Blue pH 1, combined Alcian blue-PAS, Aldehyde fuschin and combined Aldehyde fuchsin Alcian blue techniques. Results: Results were tabulated according to colour intensity into different grades ranging from + to ++++. Regarding mucin histochemistry of normal endocervical glands; the epithelium and glands show mixture of both neutral and acidic mucins. Acidic mucins are more in amount than neutral. In acidic mucins, sialomucins are predominantly seen. Conclusion: Mucin histochemical patterns serve as valuable, cost-effective tool for diagnosis in histopathology and for the researchers in histology, where a slight change in the mucin pattern may help in the early diagnosis of the disease process.